Development of HOTS-Based Flipbook Teaching Materials in Science Learning Material on Energy Sources - Erlita, Dian; Novita, Rita; Rahmatullah, Rahmatullah; Sari, Siti Mayang (Jurnal Pendidikan Humaniora, 2024)
This research is development research which aims to determine the validity of HOTS-based flipbook teaching materials in fourth grade elementary school science learning. The method used in this research is development research while the research model uses the ADDIE development research model. The subjects in this research were media expert validators, material language, educators and students. The average assessment resulting from product validity is that teaching materials experts get an average score of 97% with the criteria (Very valid), linguists get a score of 92% with the criteria (Very valid) and material experts get a score of 85 with the criteria (Very valid).